PENILAIAN DAYA TARIK OBJEK WISATA PESISIR PANTAI ARUNG BUAYA DESA MELIAH KECAMATAN SUBI KABUPATEN NATUNA - Bastian, Bastian; Erianto, Erianto; Siahaan, Sarma (Universitas Tanjungpura, 2021)
This research examines the appraisal of the attractiveness of the coastal tourist attraction of Arung Buaya, Meliah Village, Subi District, Natuna Regency, Riau Islands Province. This research was conducted in Meliah Village, Subi District, Natuna Regency using a survey method. Direct field data collection through interviews with questionnaire that given to visitors as respondents who were determined accidentally (accidental sampling). This research was conducted using the guidelines of the Director General of Forest Protection and Nature Conservation (ODTWA PHKA) in 2003 which includes 6 assessment criteria: natural beauty, beach safety / security, color of sand, variety of activities, beach cleanliness and comfort. The purpose of this study is to get value from the attractiveness of the coastal tourist attraction of Arung Buaya. The location of the tourist attraction to the center of the settlement is 3.3 km and takes 15-20 minutes to Arung Buaya Beach. The coastal area of Arung Buaya, Meliah Village, Subi District, Natuna Regency, received a score of 887.7 Category A Potential to be developed as a tourist attraction.Keywords: Assessment of Arung Buaya beach, meliah village, subi subditrict.Â AbstrakPenelitian ini mengkaji penilaian daya tarik objek wisata pantai Arung Buaya, Desa Meliah, Kecamatan Subi, Kabupaten Natuna, Provinsi Kepulauan Riau. Penelitian ini dilakukan di Desa Meliah, Kecamatan Subi, Kabupaten Natuna dengan menggunakan metode survei. Pengumpulan data lapangan langsung melalui wawancara dengan kuesioner yang diberikan kepada pengunjung sebagai responden yang ditentukan secara tidak sengaja (accidental sampling). Penelitian ini dilakukan berdasarkan pedoman Dirjen Perlindungan Hutan dan Konservasi Alam (ODTWA PHKA) tahun 2003 yang mencakup 6 kriteria penilaian yaitu keindahan alam, keselamatan/keamanan pantai, warna pasir, ragam kegiatan, kebersihan pantai dan kenyamanan. Tujuan penelitian ini adalah untuk mendapatkan nilai dari daya tarik objek wisata pesisir Arung Buaya. Jarak lokasi objek wisata ke pusat pemukiman adalah 3,3 km dan memakan waktu 15-20 menit untuk menuju Pantai Arung Buaya. Kawasan pesisir Arung Buaya, Desa Meliah, Kecamatan Subi, Kabupaten Natuna, mendapatkan nilai 887,7 Kategori A yang berpotensi untuk dikembangkan sebagai objek wisata.Kata Kunci : Arung buaya, Desa Meliah, Kecamatan Subi, Pantai, Penilaian Objek Wisata,Â Â